ANALYSIS OF THE CRAFTSMAN COCONUT BEER PRODUCTION SCENARIO USING THE SWOT TOOL - Nolli, Stefani Caroline; Pandolfi, Marcos Alberto Claudio (Revista Interface Tecnológica, 2022)
The objective of this work is to present the viability of the production, trade and distribution of a craft coconut beer in the interior of São Paulo through the strategic management tool: SWOT matrix, a term in English that refers to a set of four words: Strengths, Weaknesses , Opportunities and Threats, respectively: Strengths, Weaknesses, Opportunities and Threats. Beer is a popular drink present in people’s daily lives, with different brands, flavors and characteristics in the market, currently with a competitive and diverse market, more demanding consumers with quality and service. The coconut tree is a plant cultivated in almost all of Brazil. The work was developed through bibliographic review on websites, articles and monographs aiming at the veracity of the data obtained. The results presented demonstrate the strong production and commercialization capacity of a craft coconut beer, generating employment, income in addition to making full use of coconut derivatives.